Machinability of enamel under grinding process using diamond dental burrs. (November 2019) - Li, Quan-Zhou; Wang, Cheng-Yong; Zheng, Li-Juan; Zhao, Dan-Na; Zeng, Chao-Feng
Enamel grinding is a critical dental surgery process. However, tooth damage during the process remains a significant problem. Grinding forces, burr wear, and surface quality were characterised in relation to grinding speed, enamel orientation, grinding depth, and burr grit grain size. Results indicated that enamel rod orientation, grinding depth, and grinding speed critically affected enamel grinding. Occlusal surface grinding resulted in significantly higher normal forces, surface roughness, and marginally greater tangential forces than axial surface grinding. Damage to enamel machined surfaces indicated the significant impact of diamond grit size and rod orientation. Burr wear was primarily diamond grit peeling off and breakage. Surface roughness of axial and occlusal sections was largely influenced by grinding speed and diamond grit size. Improving the surface quality of machined enamel surfaces could be realised using fine burrs, reducing the grinding speed and grinding depth, and adjusting the feed direction vertical to the rod orientation. Enamel surface quality and roughness could be improved by reducing brittle failure and circular runout during the grinding process, respectively.